Dental age estimation of children and adolescents: Validation of the Maltese Reference Data Set. (January 2017) - Alsaffar, Hani; Elshehawi, Waleed; Roberts, Graham; Lucas, Victoria; McDonald, Fraser; Camilleri, Simon
Abstract: The purpose of this study was to validate a Reference Data Set, developed from the radiographic archives of the Dental Department, Mater Dei Hospital, Malta, for Dental Age Estimation of the Maltese population and to assess the accuracy of the method. Dental Panoramic Tomograms of 100 male and 100 females were selected. Tooth Development Stages were recorded for all 16 permanent teeth on the left and both third molars on the right. Summary and percentile data were calculated for each Tooth Development Stage and the Dental Age of each subject estimated using the unweighted average method. The distribution of the differences between the Dental and Chronological age was analysed. There was no statistically significant difference between the means of the Dental and Chronological ages and the mean differences were within acceptable limits. The conclusion was that the Dataset is valid for the Maltese population and the method used gives adequate accuracy. Highlights: The Maltese RDS has been validated. The large, ethnically homogenous sample results in increased accuracy. The simple weighted average method gives an accurate estimation of age.